Long-term outcomes of prostate intensity-modulated radiation therapy incorporating a simultaneous intra-prostatic MRI-directed boost - Laughlin, Brady S.; Silva, Alvin C.; Vora, Sujay A.; Keole, Sameer R.; Wong, William W.; Schild, Michael H.; Schild, Steven E. (Frontiers in Oncology, 2022)
Purpose/Objectives: This retrospective study demonstrates the long-term outcomes of treating prostate cancer using intensity modulated (IMRT) with incorporation of MRI directed boost. Materials/Methods: From February 2009 to February 2013, 78 men received image guided IMRT delivering 77.4 Gy in 44 fractions with simultaneously integrated boost to 81-83 Gy to an MRI identified lesion. Patients with intermediate risk or high-risk prostate cancer were recommended to receive 6 months and 24-36 months of adjuvant hormonal therapy, respectively. Results: Median follow-up was 113 months (11 – 147). There were 18 low risk, 43 intermediate risk, and 17 high risk patients per NCCN risk stratification included in this study. Adjuvant hormonal therapy was utilized in 32 patients (41%). The 10-year biochemical control rate for all patients was 77%. The 10-year biochemical control rates for low risk, intermediate risk and high-risk diseases were 94%, 81%, and 88%, respectively (p=0.35). The 10-year rates of local control, distant control and survival were 99%, 88%, and 66%, respectively. Of 25 patients who died, only 4 (5%) died of prostate cancer. On univariate analysis, T-category and pre-treatment PSA level were associated with distant failure rate (p = 0.02). There was no Grade >3 genitourinary and gastrointestinal toxicities that persisted at last follow-up. Conclusions: This study demonstrated the long-term efficacy of using MRI to define an intra-prostatic lesion for SIB to 81- 83Gy while treating the entire prostate gland to 77.4Gy with IMRT. Our study confirms that modern MRI can be used to locally intensify dose to prostate tumors providing high long-term disease control while maintaining favorable long-term toxicity.